2020
DOI: 10.3390/su13010209
|View full text |Cite
|
Sign up to set email alerts
|

Green Purchase Behavior: The Effectiveness of Sociodemographic Variables for Explaining Green Purchases in Emerging Market

Abstract: Environmental degradation is a serious problem in modern civilization as it causes changes in consumer behavior towards ecologically responsible purchasing. In order to understand the green product purchasing decision process, an extensive literature review on green purchasing behavior was conducted. The current study is an exploratory research and the purpose of this paper was to investigate how sociodemographic factors explain consumers’ green purchase behavior. The differences between gender, age, education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 89 publications
3
69
1
1
Order By: Relevance
“…Nevertheless, previous studies have shown that consumers are more positive about the environment (Han, 2020;Witek & Kuźniar, 2021), however, no evidence shows that the demand for green products and services has increased. Despite the favorable attitude of consumers towards the environment, the environmental-friendly product share is still reported 1 to 3% of the whole market (Bray, Johns, & Kilburn, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, previous studies have shown that consumers are more positive about the environment (Han, 2020;Witek & Kuźniar, 2021), however, no evidence shows that the demand for green products and services has increased. Despite the favorable attitude of consumers towards the environment, the environmental-friendly product share is still reported 1 to 3% of the whole market (Bray, Johns, & Kilburn, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Consumers who are more knowledgeable about the environment show a higher tendency to act positively on environmental issues [20,21]. However, the positive views of young consumers towards environmental protection are not always reflected in their activities [76,77]. It is also worth emphasizing that, according to some research, young people, especially those aged 18-24, care the least to be perceived as environmentally friendly [78,79].…”
Section: Resultsmentioning
confidence: 99%
“…Research on this topic began in the 1970s, with researchers from Sweden, Japan, and the UK contributing significantly to the subject over the past decade. Previous research has focused on the green purchase behavior [32,33], change and diversity in patterns of usage, policies calling for a behavior change [34,35], and green consumption [36,37]. The World Population Review [38] expresses the importance of achieving SD through choices, lifestyles, and behavior.…”
Section: Theoretical Frameworkmentioning
confidence: 99%